A multi-objective agile project planning model and a comparative meta-heuristic approach - SENNAROĞLU, BAHAR; ALABAŞ USLU, ÇİĞDEM; TUZKAYA, GÜLFEM (My University, 2022)
Agile software development methodologies are used to meet the changing needs in the market. The most popular framework among these methodologies is the Scrum framework. In Scrum planning, the assignment of user stories to sprints requires the consideration of multiple objectives to use the limited resources more effectively. In this paper, a multi-objective mixed-integer programming model is developed which considers three objectives: maximizing the sprint capacity usage, maximizing the assignment of user stories with high priority to primary sprints, and maximizing the assignment of affine user stories to the same sprint. The aim is to contribute to both theory and practice of Scrum planning considering multiple objectives. Additionally, different from the existing literature of Scrum planning, alternative user stories are also taken into account. The proposed model is applied to the small, medium, and big-sized instances of the problem taken from a real-life system. Non-dominated Sorting Genetic Algorithm (NSGA-II) and Strong Pareto Evolutionary Algorithm (SPEA2) are used as heuristic approaches since big-sized instances of the problem could not be solved using optimization approaches. To analyze the performances of these algorithms, Hypervolume (HV), Epsilon (epsilon), Generational Distance (GD), Inverted Generational Distance (IGD), Inverted Generational Distance Plus (IGD+), and Spread (Delta) indicators are used. Results showed that NSGA-II performs better than SPEA2 according to e indicator for big-sized instance. On the other hand, SPEA2 performs better than NSGA-II according to HV, GD, IGD, IGD+, and Delta indicators. However, the results are very close to each other for HV, epsilon, IGD, and IGD+ indicators. In conclusion, both algorithms can be used to deal with the multi-objective Scrum planning problem.
Keywords: Bilgisayar Bilimleri; Bilgi Güvenliği ve Güvenilirliği; Veritabanı ve Veri Yapıları; Mühendislik ve Teknoloji; Computer Sciences; Information Security and Reliability; Database and Data Structures; Engineering and Technology; BİLGİSAYAR BİLİMİ, BİLGİ SİSTEMLERİ; Bilgisayar Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); BİLGİSAYAR BİLİMİ, YAZILIM MÜHENDİSLİĞİ; COMPUTER SCIENCE, INFORMATION SYSTEMS; COMPUTER SCIENCE; Engineering, Computing & Technology (ENG); COMPUTER SCIENCE, SOFTWARE ENGINEERING; Yazılım; Bilgi sistemi; Bilgisayar Bilimi Uygulamaları; Bilgisayar Bilimi (çeşitli); Genel Bilgisayar Bilimi; Fizik Bilimleri; Software; Information Systems; Computer Science Applications; Computer Science (miscellaneous); General Computer Science; Physical Sciences; Agile software development; Sprint planning; Scrum; Multi-objective model; NSGA-II; SPEA2; OPTIMIZATION; ALGORITHM